Left-Sided Catamenial Pneumothorax Associated with Diaphragmatic Fenestrations - Seok, Yangki; Lee, Eungbae (The Thoracic and Cardiovascular Surgeon, 2013)
Catamenial pneumothorax is a rare disorder with an unknown etiology. It is characterized by recurrent spontaneous pneumothorax during or preceding menstruation. One proposed mechanisms is diaphragmatic fenestration. The majority of catamenial pneumothorax is right sided. We report a left-sided catamenial pneumothorax associated with multiple diaphragmatic fenestrations.
Keywords: catamenial pneumothorax; diaphragmatic fenestration; thoracoscopy/video-assisted thoracic surgery